LEAF ARCHITECTURE OF THE AVERRHOA COLLECTION AT BOGOR BOTANICAL GARDEN - Canita, Anggun; Almaidah, Elsa Nadia; Damayanti, Inggar; Santoso, Trio; Hariri, Muhammad Rifqi (Forestry Study Program University Of Mataram, 2025)
The Bogor Botanical Garden (KRB) is a significant conservation site in Indonesia, serving as a sanctuary for a diverse range of plant species, including the genus Averrhoa, which holds both economic and ecological value. Plant morphology studies are essential for species classification and biodiversity conservation. This study aims to identify the morphological characteristics of leaves from three Averrhoa species (Averrhoa bilimbi, Averrhoa carambola, and Averrhoa dolichocarpa) as a tool for field identification. Conducted at the Morphology, Anatomy, and Cytology Laboratory of the Bogor Botanical Garden, the research utilized visual observation and digital microscopy to analyze key leaf traits. Principal Component Analysis (PCA) and cluster analysis revealed significant differences in adaxial leaf color and lamina shape, although certain characteristics, such as abaxial color and leaf margin type, were similar across species. These findings demonstrate that leaf architecture is an effective means of identifying Averrhoa species and contribute to taxonomy and biodiversity conservation efforts. Further research is recommended to expand sampling and explore genetic correlations.